The best of letterhead & logo design. - Hewes, Rachel; Hodges, Allison (Rockport Publishers, 2012)
The best-selling Letterhead and Logo Design now compiles the most creative and inspiring work in the field in a stunning collection featuring the best of the past four volumes.